2015
DOI: 10.1016/j.cma.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

A scalable, matrix-free multigrid preconditioner for finite element discretizations of heterogeneous Stokes flow

Abstract: International audienceIn this paper we describe a computational methodology that is specifically designed for studying three-dimensional geodynamic processes governed by heterogeneous visco-plastic Stokes flow. The method employs a hybrid spatial discretization consisting of a View the MathML sourceQ2-P1disc mixed finite element formulation for the Stokes problem, coupled to a material-point formulation which is used for representing material state and history-dependent variables. The applicability and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
130
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 73 publications
1
130
0
Order By: Relevance
“…The primary concern is how to best represent the coefficient structure on the coarse grids. When the coefficients are highly variable, hybrid strategies which employ different techniques to define the coarselevel operators have proven to yield improved time-to-solution with minimal storage overhead [16,27].…”
Section: Example Use Casesmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary concern is how to best represent the coefficient structure on the coarse grids. When the coefficients are highly variable, hybrid strategies which employ different techniques to define the coarselevel operators have proven to yield improved time-to-solution with minimal storage overhead [16,27].…”
Section: Example Use Casesmentioning
confidence: 99%
“…The depth of the multigrid hierarchy might be shallower than the equivalent sequential hierarchy, and thus an iterative solver on the "coarsest" level should be used. In practice it is observed that an inexact coarse-level solve up to a specified tolerance can yield an optimal multigrid preconditioner [16,28]. However, the cost of obtaining a fixed-precision inexact solve could be n k log n k and given the shallow nature of the hierarchy, this cost may be sufficient to degrade the expected O(n) time-to-solution.…”
mentioning
confidence: 99%
See 3 more Smart Citations